As-Sīmiyāiyah Li Ferdinand De Saussure Fī Riwāyah ‘Asākir Qous Quzh Li Andrea Hirata (Al-Qiyam al-Islāmiyah Anmudzajan) - Riyadi, Agus; Bahri, Samsul; Parida, Hasna; Azhari, Faiz (Universitas Muhammadiyah Gorontalo, 2023)
In the novel